INFECTION OF SHEEP WITH INTESTINAL CESTODES IN UZBEKISTAN: EPIZOOTIOLOGICAL ANALYSIS, ECOLOGICAL FACTORS, AND PREVENTIVE MEASURES - Avezimbetov Shavkat; Bauaddinov Kamaladdin Karamaddinovich; Azada Yakupbay qizi Khojamuratova (The latest news and research in education, 2025)
This article examines the infection of sheep with intestinal cestodes in the conditions of Uzbekistan, including the spread of monieziosis, thysanieziosis, and avitellinosis, as well as the degree of invasion depending on age and seasonal conditions. The results of the study indicate that the highest levels of monieziosis infection are observed in the spring and autumn seasons, while the degree of invasion decreases in summer. It has also been established that the activity of oribatid (soil) mites, which serve as intermediate hosts for monieziosis pathogens, depends on climatic conditions. The article provides recommendations for the diagnosis and prevention of monieziosis, as well as seasonal deworming and preventive measures based on the results of parasitological examinations.